Imersão na visualização científica: utilizando um ambiente virtual imersivo para interação com dados climáticos - Fernandes, Raul Felipe de Morais (2017)
Data representation methods play an important role in any area of study, since understanding information in a research context is essential for any scientific advancement. In this sense, the area of Scientific Visualization is highlighted by proposing efficient means to improve the observer’s perception of a dataset. In meteorology field, for example, complex visual information about distinct climatic events are analyzed as datasets in numerous surveys. The variety of complex climatic phenomena, each requiring its own intuitive visual representations to convey the correct impressions end up bringing some challenges to apply Scientific Visualization in this area. In this way, it is necessary to investigate alternatives that can improve the forms of visualization within this context. Virtual Reality has been increasingly used as an alternative tool for non-conventional representations as it becomes more accessible. The concept of immersive Virtual Environments has been applied to improve the experience of users in the context of teaching and learning by providing greater level ofconcentration and freedom to explore the information presented. According tothese facts,this paper presents a study on the use of the Scientific Visualization of Climate Data in immersive Virtuals Environments, in order to identify how Virtual Reality can bring benefits to the understanding of complex data representations. For this, an application was developed for immersive visualization of meteorological information, followed by an evaluation with experts related to the use of these concepts in meteorology context.